2021
DOI: 10.1200/jco.2021.39.15_suppl.3584
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 first-in-human study of the anti-LAG-3 antibody MK4280 (favezelimab) plus pembrolizumab in previously treated, advanced microsatellite stable colorectal cancer.

Abstract: 3584 Background: Patients (pts) with microsatellite stable (MSS) metastatic colorectal cancer (mCRC) that progressed on ≥2 prior therapies have limited treatment options, with median OS ranging from 6-9 months (mo). In the dose-escalation phase of this first-in-human multicohort study (NCT02720068), the anti-lymphocyte activation gene (LAG)-3 antibody favezelimab (fave) was well tolerated alone and with pembrolizumab (pembro) across all dose levels (Lakhani, SITC, 2018, abstract O26). Here, we evaluate the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 0 publications
0
19
3
Order By: Relevance
“…Several clinical studies are investigating the potential role of immune checkpoint inhibitors in combination with chemotherapy, including combinations with antiangiogenic drugs (monoclonal antibodies and multikinase inhibitors); anti-EGFR monoclonal antibodies; inhibitors of intracellular signal-transduction pathways, including KRAS G12C, BRAF V600E, or MEK inhibitors; or radiotherapy. 129,[171][172][173][174][180][181][182][183][184][185][186][187][188][189][190] Although promising signs of therapeutic activity have been observed in some of these studies, further translational and clinical investigation is needed to identify the most effective combination strategies as well to appropriately select the patients who could obtain a clinical benefit from this approach.…”
Section: Integrating Immunotherapies In the Continuum Of Care Of Meta...mentioning
confidence: 99%
“…Several clinical studies are investigating the potential role of immune checkpoint inhibitors in combination with chemotherapy, including combinations with antiangiogenic drugs (monoclonal antibodies and multikinase inhibitors); anti-EGFR monoclonal antibodies; inhibitors of intracellular signal-transduction pathways, including KRAS G12C, BRAF V600E, or MEK inhibitors; or radiotherapy. 129,[171][172][173][174][180][181][182][183][184][185][186][187][188][189][190] Although promising signs of therapeutic activity have been observed in some of these studies, further translational and clinical investigation is needed to identify the most effective combination strategies as well to appropriately select the patients who could obtain a clinical benefit from this approach.…”
Section: Integrating Immunotherapies In the Continuum Of Care Of Meta...mentioning
confidence: 99%
“…An increase in reliable clinical data on the double blocking of LAG-3 and PD-1 has prompted people to focus on this combination immunotherapy. A clinical trial (NCT02720068) [ 221 ] demonstrated that the combination of LAG-3 inhibitor (Favezelimab) and Pembrolizumab exhibits good antitumor activity, especially in patients with PD-L1 CPS ≥ 1.…”
Section: The Exploration Of Clinical Strategies For Icb Therapy and R...mentioning
confidence: 99%
“…Exploratory analyses showed that patients presenting plasma TMB of 28 variants per megabase or more (21% of MSS tumors) had the greatest OS benefit (hazard ratio [HR]: 0.34, p = 0.004). Results from the phase I first-in-human clinical trial testing the anti-LAG-3 antiboy favezelimab and the anti-PD-1 pembrolizumab in previously treated patients with advanced MSS CRC were recently reported [ 12 ]. Of 89 patients receiving the combined blockade, four patients presented partial response and one patient achieved complete response.…”
Section: Immunotherapy-based Combinations In Pmmr/mss Mccrmentioning
confidence: 99%